1995
DOI: 10.1111/j.1464-5491.1995.tb00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Mortality of Childhood‐onset Insulin‐dependent Diabetes Mellitus in Leicestershire: 1940–1991

Abstract: The relative risk of death by calendar date of diagnosis was investigated in a population-based incident cohort of 845 (463 males:382 females) IDDM diagnosed in Leicestershire before the age of 17 years between 1940 and 1989. The mortality status of 844 (99.9%) patients was determined as of the 31 December 1991, representing 14,346 person-years of risk. Trends in relative risk of death were investigated using Cox proportional hazards modelling for within cohort comparisons and age/sex and calendar time adjuste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 26 publications
2
33
1
2
Order By: Relevance
“…Several studies have reported decreasing mortality rates in longterm follow-up of cohorts diagnosed during the 1960s and 1970s [5,8,[16][17][18]. A newly published systematic review assessing mortality in type 1 diabetes documented less marked excess mortality in more recent studies [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported decreasing mortality rates in longterm follow-up of cohorts diagnosed during the 1960s and 1970s [5,8,[16][17][18]. A newly published systematic review assessing mortality in type 1 diabetes documented less marked excess mortality in more recent studies [19].…”
Section: Introductionmentioning
confidence: 99%
“…175, [177][178][179][180][181] To examine the validity of these model estimates, life expectancy was calculated using life table methods by adjusting the UK life table to take into account the higher relative risk of mortality among people with type 1 diabetes. The relative risks for this analysis were taken from a study that selected 7713 type 1 diabetes patients and compared them to 38,518 non-diabetic patients.…”
mentioning
confidence: 99%
“…The mortality in Allegheny County was five times higher than that of the general population (3)(4)(5). European reports of population-based studies from Norway (6) and the U.K. (7,8) suggest that the mortality of children with type 1 diabetes was two to three times higher than that of the general population. The report from the U.K. also noted that the standardized mortality ratios (SMRs) decreased from 981 to 238 during the period 1940 -1989 (8).…”
mentioning
confidence: 99%